Diabetes insipidus secondary to sellar/parasellar lesions. (26th March 2021) - Angelousi, Anna; Mytareli, Chrysoula; Xekouki, Paraskevi; Kassi, Eva; Barkas, Konstantinos; Grossman, Ashley; Kaltsas, Gregory
Abstract: Diabetes insipidus (DI) is a well‐recognised transient or permanent complication following transsphenoidal surgery for pituitary adenomas or other sellar/parasellar lesions. However, data regarding the prevalence of pre‐operative DI in sellar/parasellar lesions other than pituitary adenomas are scarce. We systematically reviewed the existing data for defining the prevalence of DI before any treatment in adult patients with sellar/parasellar lesions, excluding pituitary adenomas and metastatic lesions. In total, 646 patients with sellar/parasellar lesions presenting with DI at diagnosis were identified. The most common pathologies of sellar/parasellar lesions presenting with DI at diagnosis were lymphocytic hypophysitis (26.5%), craniopharyngiomas (23.4%), Langerhans's cell histiocytosis (18.9%) and Rathke's cleft cyst (12.7%), accounting for the vast majority (more than 80%) of these lesions. Overall, DI at diagnosis was found in 23.4% of all patients with sellar/parasellar lesions, albeit with a wide range from 10.6% to 76.7%, depending on the nature of the pathology. The highest prevalence of DI was found in less commonly encountered lesions namely germ‐cell tumours (76.7%), abscesses (55.4%) and neurosarcoidosis (54.5%), each accounting for less than 3% of all sellar/parasellar lesions. Most DI cases (68.8%) were associated with anterior pituitary hormonal deficiencies, in contrast to pituitary adenomas that rarely present with DI. The enlargement and enhancement of the pituitary stalk were the most common findings on magnetic resonance imaging besides the loss of the high signal of the posterior pituitary on T1‐weighted images. Resolution of DI spontaneously or following systemic and surgical management occurred in 22.4% of cases. Post‐operative DI, not evident before surgery, was found in 27.8% of non‐adenomatous sellar/parasellar lesions, and was transient in 11.6% of them. Besides distinctive imaging features and symptoms, early recognition of DI in such lesions is important because it directs the diagnosis towards a non‐adenomatous sellar/parasellar tumour and the early initiation of appropriate treatment. Abstract : Diabetes insipidus can be found in up to 23.4% of all non‐adenomatous sellar/parasellar lesions at presentation. Lymphocytic hypophysitis, craniopharyngioma, Langerhans's Cell Histiocytosis and Rathke's cleft cyst were by order the most frequent pathologies. Recovery of DI diagnosed at presentation was found in 22.4% of cases after either surgical or medical treatment, or in some cases spontaneously.